Developing a Core Outcome Set for Cesarean Delivery Maternal Infectious Morbidity Outcomes - Briscoe, Kristin E.; Haas, David M. (American Journal of Perinatology, 2020)
Objective This study aimed to develop a core outcome set of primary outcomes for studies involving cesarean deliveries with infectious morbidity outcomes.Study Design Authors reported primary outcomes from 11 Cochrane systematic reviews (SRs), 12 other SRs, and 327 randomized controlled trials (RCTs). These outcomes were condensed into 20 primary outcome groups. Next, a modified Delphi technique was used to gain consensus on key outcomes. Authors from included SRs were sent a questionnaire consisting of a free response and multiple-choice questions. These data were used to propose a set of core outcomes.Results The most frequent outcomes in RCTs were composite “infectious outcomes” (24%) with the second most common being endometritis (12%). The most common reported SR outcomes were wound infection (21%) and endometritis (16%). For the Delphi survey free response portion, wound infection (88%) and endometritis (79%) were the most commonly endorsed outcomes. Chosen list outcomes were maternal mortality (83%), wound infection (83%), wound complications (86%), and postpartum endometritis (80%). The proposed final core outcome set for cesarean trials was endometritis (primary outcome), maternal mortality, wound infection, wound complications, febrile morbidity, and neonatal morbidity.Conclusion Utilizing defined core outcomes in all studies of cesarean section can harmonize trial reports and allow data synthesis for meta-analyses.
Keywords: cesarean delivery; pregnancy; infection; systematic review; core outcomes